A Garbage Can Model of Organizational Choice - Cohen, Michael D.; March, James G.; Olsen, Johan P. (Administrative Science Quarterly, 1972)
Organized anarchies are organizations characterized by problematic pre ferences, unclear technology, and fluid participation. Recent studies of universities, a familiar form of organized anarchy, suggest that su ch organizations can be viewed for some purposes as collections of cho ices looking for problems, issues and feelings looking for decision si tuations in which they might be aired, solutions looking for issues to which they might be an answer, and decision makers looking for work. These ideas are translated into an explicit computer simulation model of a garbage can decision process. The general implications of such a model are described in terms of five major measures on the process. Po ssible applications of the model to more narrow predictions are illust rated by an examination of the model's predictions with respect to the effect of adversity on university decision making.